Piła (Schneidemühl ) czy Frankfurt nad Odrą? Spór o nową stolicę niemieckiej Marchii Wschodniej (Ostmark) w latach 1919-1939 = Piła (Schneidemühl ) or Frankfurt /Oder? The controversy about the new capital of the German Ostmark 1919-1939 - Kiec, Olgierd (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Eastern territories of Prussia with its large Polish population, where widely known in the 19 century as "Eastern March" (Ostmark). Poznań (Posen) was regarded as the informal capital of the Ostmark. The Treaty of Versailles granted the Prussian provinces Posen and Westpreussen to Poland, but small parts of both provinces remained in Germany.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia